2012
DOI: 10.1186/1752-1947-6-269
|View full text |Cite
|
Sign up to set email alerts
|

Pure choriocarcinoma of the testis presenting with jaundice: a case report and review of the literature

Abstract: IntroductionTesticular cancer is the most common malignancy in men 15- to 35-years-old. The North American standard classification divides testicular cancers into germ cell tumors and non-germ cell tumors. The lymphatic spread of germ cell tumors usually involves the retroperitoneal lymph nodes. However, this spread to the retroperitoneum rarely involves the hepatic hilum. We describe an unusual case of metastatic choriocarcinoma of the testis that was clinically mimicked by a cholestatic jaundice. This is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
8
0
1
Order By: Relevance
“…Cisplatinbased chemotherapy is the cornerstone of treating patients with metastatic non-seminomatous germ cell tumours [14]. However, other clinicians in case reports have found that pure choriocarcinomas are not as sensitive to chemotherapy as NSGCTs, possibly because of their high malignant potential and poor prognosis which is associated with early hematogenous metastasis and its associated complications [17] which this report confirms. When this kind of tumour is diagnosed early, it responds well to chemotherapy.…”
Section: Discussionsupporting
confidence: 73%
“…Cisplatinbased chemotherapy is the cornerstone of treating patients with metastatic non-seminomatous germ cell tumours [14]. However, other clinicians in case reports have found that pure choriocarcinomas are not as sensitive to chemotherapy as NSGCTs, possibly because of their high malignant potential and poor prognosis which is associated with early hematogenous metastasis and its associated complications [17] which this report confirms. When this kind of tumour is diagnosed early, it responds well to chemotherapy.…”
Section: Discussionsupporting
confidence: 73%
“…In the past almost 4 decades, pure CC of the testis has only been the subject of case reports. [6][7][8][9] Contemporary clinical and pathologic information of pure CC of the testis, particularly in this era of chemotherapy as a standard for GCT, is limited. It is also unclear whether testicular GCT with a predominant CC component will have a similar behavior to pure CC and how the predominant CC component will impact the pathologic variables in a mixed GCT.…”
mentioning
confidence: 99%
“…However, occasionally in this context or more frequently when extensive, predominant, or pure, CC presents as metastatic disease, with symptoms related to hemorrhagic metastasis (hemoptysis, melena, intracranial hemorrhage, etc.) [149][150][151][152]. In these cases, a clinically evident primary may not be readily apparent.…”
Section: Clinical Presentationmentioning
confidence: 90%